GAMBARAN KETERAMPILAN MENYIKAT GIGI DENGAN PENURUNAN INDEKS PLAK PADA SISWA/I SDN 123 HUTABARGOT DOLOK - Yenny Lisbeth Siahaan; Nelly Katarina Manurung; Sondang (Poltekkes Kemenkes Medan, 2022)
Brushing teeth is intended to remove plaque from tooth surface in order to forestall the incidence of plaque accumulation. Skill in brushing teeth is generally suggested to remove soft deposit from tooth surface so that the accumulation of plaque can be avoided. The objective of the research was to find out the skill in brushing teeth on decreasing plaque index in the students of SN 123 Hutabargot Dolok, in 2015.The research was a descriptive survey which was performed by direct examination on plaque index. The population was 160 students, and16 of them were used as the samples. The result of the research showed that there was the difference in plaque index value in the respondents. Before the counseling about the skill in brushing teeth was provided, none of the respondents (0%) had good knowledge, 2 of them (12.5%) had moderate knowledge, and 14 of them (87.5%) had bad knowledge. After the counseling, 2 respondents (12.5%) had good knowledge, 8 respondents (50%) had moderate knowledge, and 6 respondents (37.5%) had bad knowledge. The conclusion of the research was that counseling about the skill in brushing teeth for the students at SDN 123 Hutabargot Dolok, in 2015, had increased their knowledge of brushing teeth. It is recommended that dental nurses provide counseling about dental and oral health, especially about the skill in good and correct tooth brushing so that dental and oral health can be maintained.